2007
DOI: 10.1007/s11517-007-0217-7
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed tool for intra-tracheal temperature and humidity assessment in laryngectomized individuals: the Airway Climate Explorer (ACE)

Abstract: The aim of this study is to develop a postlaryngectomy airway climate explorer (ACE) for assessment of intratracheal temperature and humidity and of influence of heat and moisture exchangers (HMEs). Engineering goals were within-device condensation prevention and fast response time characteristics. The ACE consists of a small diameter, heated air-sampling catheter connected to a heated sensor house, containing a humidity sensor. Air is sucked through the catheter by a controlled-flow pump. Validation was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…6) decays exponentially, similar to previously described in vivo AH insp measurements. 6,13,15 Weight change (see Fig. 5) increases linearly for small volumes and then levels off.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…6) decays exponentially, similar to previously described in vivo AH insp measurements. 6,13,15 Weight change (see Fig. 5) increases linearly for small volumes and then levels off.…”
Section: Discussionmentioning
confidence: 96%
“…In such measurements extreme care is required to avoid loss of water vapor due to condensation in the sampling tube. 12,13 No commercial equipment is available for these challenging measurements, and experience has shown that custom-built equipment is difficult to develop and maintain. 12,13 Moreover, only a minority of available HMEs thus far have been analyzed both in vitro and in vivo.…”
Section: See the Related Editorial On Page 1559mentioning
confidence: 99%
See 3 more Smart Citations